Model reference adapted control of the short run exchange rate of the TNT dollar - St. Clair King, Mary ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 1996)
Introduces a modelling technique based on the short run relationships of the exchange rate, with particular reference to the role of the central bank in exercising control, and the effects of speculation.